Research Handbook of Marketing in Emerging Economies 2017
DOI: 10.4337/9781784713171.00014
|View full text |Cite
|
Sign up to set email alerts
|

Perceived advertising intrusiveness and avoidance in emerging economies: The case of China

Abstract: The version in the Kent Academic Repository may differ from the final published version. Users are advised to check http://kar.kent.ac.uk for the status of the paper. Users should always cite the published version of record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…Reactance theory discusses the importance of freedom in making choices by illustrating it through the ways in which individuals reject or fight messages that are considered persuasive or invade their personal space (Brehm & Brehm, 1981). A similar view is also expressed by (Petrovici et al, 2017) where the importance of freedom in choosing something can cause a person to react to stimuli that are considered to interfere with their personal space. So if there is a stimulus in the form of a message that is considered to attack the individual's personal space, it can trigger a psychological reactance in the form of an unpleasant motivational state (Brehm and Brehm, 1981).…”
Section: Literature Review Theoretical and Conceptual Backgroundmentioning
confidence: 91%
“…Reactance theory discusses the importance of freedom in making choices by illustrating it through the ways in which individuals reject or fight messages that are considered persuasive or invade their personal space (Brehm & Brehm, 1981). A similar view is also expressed by (Petrovici et al, 2017) where the importance of freedom in choosing something can cause a person to react to stimuli that are considered to interfere with their personal space. So if there is a stimulus in the form of a message that is considered to attack the individual's personal space, it can trigger a psychological reactance in the form of an unpleasant motivational state (Brehm and Brehm, 1981).…”
Section: Literature Review Theoretical and Conceptual Backgroundmentioning
confidence: 91%
“…Several other research studies emphasize the cognitive dimension of intrusiveness. Petrovici et al (2017) expands the concept of ad intrusiveness and regarded it as a perception that interrupts the cognitive processes of the audience during their engagement in TV programs. Youn and Kim (2019) observe the empirical connection between ad intrusiveness and reactance.…”
Section: Intrusivenessmentioning
confidence: 99%
“…But there has been an erosion of trust (Petrovici et al , 2017; Briñol et al , 2015; Blades et al , 2014) in mainstream advertising which has indicated advertising’s deteriorating impact as the chief source of brand discovery. Cynicism with advertising has been steadily growing over the decades (Zanot, 1984).…”
Section: Literature Reviewmentioning
confidence: 99%